Cytokine-induced macropinocytosis in macrophages is regulated by 14-3-3ζ through its interaction with serine-phosphorylated coronin 1 - Gupta S.B.; Moes S.; Jenoe P.; Pieters J. (My University, 2025)
The induction of macropinocytosis in macrophages during an inflammatory response is important for clearance of pathogenic microbes as well as the generation of appropriate immune responses. Recent data suggest that cytokine stimulation of macrophages induces macropinocytosis through phosphorylation of the protein coronin 1, thereby redistributing coronin 1 from the cell cortex to the cytoplasm followed by the activation of phosphoinositol-3 (PI-3) kinase. However, how coronin 1 phosphorylation regulates these processes remains unclear. We here define an essential role for 14-3-3ζ in cytokine-induced and coronin-1-dependent macropinocytosis in macrophages. We found that, upon stimulation, phosphorylated coronin 1 transiently associated with 14-3-3ζ and receptor of activated C kinase 1 (RACK1). Importantly, downregulation of 14-3-3ζ, but not RACK1, prevented relocation of coronin 1, as well as the induction of PI-3 kinase activity and thereby macropinocytosis upon cytokine stimulation. Together these data define an essential role for 14-3-3ζ in the regulation of macropinocytosis in macrophages upon cytokine stimulation through modulation of the localization of coronin 1. Macropinocytosis is an important process in immunity that permits macrophages and dendritic cells to sample their environment for antigens. Recent studies have also highlighted the importance of macropinocytosis in the endocytosis and degradation of infectious and particulate material. However, the molecular processes by which macropinocytosis is regulated are not well understood. In this Editor's Choice article, BoseDasgupta and colleagues highlight the critical role of 14-3-3ζ in relocating serine-phosphorylated coronin 1 in response to inflammatory stimuli to promote macropinocytosis. This article is accompanied by a podcast, listen now. Or listen in iTunes. © 2015 FEBS.